Microwave-Assisted Synthesis of Pd-MWCNT/TiO2 Catalysts and its Application in the Photodegradation of Reactive Black B - Ye, Shu; Ullah, Kefayat; Zhu, Lei; Bok Jo, Sun; Oh, Won-Chun (Asian Journal of Chemistry, 2014)
MWCNT-TiO2 and Pd-MWCNT/TiO2 composites were prepared via a controlled and energy efficient microwave assisted method and their high photocatalytic activity was evaluated by the degradation of reactive black B solutions (RBB) under visible light. The surface structure, crystal phase and elemental identification of these composites were characterized by SEM, TEM, XRD, EDX and UV-visible, respectively. The degradation of reactive black-B solution was determined using UV-visible spectrophotometry. These as-prepared photocatalysis were used for H2 evolution under visible light irradiation. An increase in photocatalytic activity was observed and it may attribute to the increase of the photo-absorption effect by the MWCNT and the cooperative effect of Pd element.